1988
DOI: 10.2118/13532-pa
|View full text |Cite
|
Sign up to set email alerts
|

Application of Preconditioned Conjugate-Gradient-Like Methods in Reservoir Simulation

Abstract: ·Conjugate-gradient-like (CGL) methods were used to solve the matrix equations for several large-field and fine-grid models. The methods used incomplete LU (lLU) or modified incomplete LU (MILU) preconditioning coupled with orthomin acceleration. The CGL methods were applied to the original matrix or to a reduced system from red/black ordering. Test results from a black-oil model with fault throws, a fractured reservoir model, and three steamflood models are given. It was found that the CGL methods are effecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1990
1990
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…the convergence behavior of preconditioned conjugate gradient methods. There have been many studies of the use of various ordering techniques coupled with incomplete LU (ILU) factorization preconditioners [3,4,5,7,11,12,13,15,16,17,25,29,30,34,35,38,39].…”
Section: Introduction It Is Well Known That the Ordering Of The Unknmentioning
confidence: 99%
See 2 more Smart Citations
“…the convergence behavior of preconditioned conjugate gradient methods. There have been many studies of the use of various ordering techniques coupled with incomplete LU (ILU) factorization preconditioners [3,4,5,7,11,12,13,15,16,17,25,29,30,34,35,38,39].…”
Section: Introduction It Is Well Known That the Ordering Of The Unknmentioning
confidence: 99%
“…Reduced systems are very eective (red/black ordering of a bipartite graph, and exact elimination of the red nodes). Incomplete factorizations can be classied by the allowed level of ll [17,29,38,39]. A rigorous denition of the level is given in x 2.2 .…”
Section: Introduction It Is Well Known That the Ordering Of The Unknmentioning
confidence: 99%
See 1 more Smart Citation
“…Many preconditioned conjugate gradient type methods use incomplete lower-upper factorization (ILU), which is similar to Gaussian elimination except that decomposition is terminated at a certain level of fill. Previous studies have shown that an increase in the level of fill (Q produces higher-quality preconditioning, which therefore reduces the number of iterations required for convergence [e.g., Simon, 1988;Northrup and Woo, 1988]; however, an increase in the level of fill requires more work per iteration, and consequently it may not be costeffective. Generally, the optimal level of fill is •' -1, 2, or 3 for two-dimensional problems and •' = 0 or 1 for threedimensional problems.…”
Section: Matrix Solution Algorithmmentioning
confidence: 99%